TARGETING THE TUMOR MICRO-ENVIRONMENT: NANOPARTICLE-MEDIATED DELIVERY OF IMMUNOMODULATORY DRUGS TO ENHANCE CANCER IMMUNOTHERAPY - Ali, Omar; Mohamed, Ahmed; Hassan, Mariam (Yayasan Adra Karima Hubbi, 2025)
The tumor micro-environment plays a central role in regulating antitumor immune responses and represents a major barrier to the effectiveness of cancer immunotherapy. Immunosuppressive cellular components, abnormal vasculature, and inhibitory cytokine networks often limit immune cell infiltration and reduce the efficacy of systemically administered immunomodulatory drugs. This study aims to investigate nanoparticle-mediated delivery strategies to selectively target the tumor micro-environment and enhance cancer immunotherapy outcomes. An experimental nanomedicine approach was employed, involving the design and characterization of drug-loaded nanoparticles, evaluation of biodistribution and tumor localization, and assessment of immunological responses in tumor models. Nanoparticle performance was compared with free drug administration to determine delivery efficiency and therapeutic impact. The results demonstrate that nanoparticle-mediated delivery significantly improved accumulation of immunomodulatory drugs within tumor tissues, leading to enhanced cytotoxic T cell infiltration, reduced immunosuppressive cell populations, and improved antitumor efficacy. Targeted delivery also reduced off-target immune activation and systemic toxicity compared to conventional administration. In conclusion, nanoparticle-based targeting of the tumor micro-environment offers an effective strategy to overcome immunosuppressive barriers and amplify the therapeutic potential of cancer immunotherapy. This approach provides a promising framework for the development of next-generation precision immuno-oncology treatments.